2021
DOI: 10.37989/gumussagbil.887800
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Knowledge Level of University Students on Dyslexia (Gümüşhane University Example)

Abstract: Bu araştırma üniversite öğrencilerinin disleksi hastalığı hakkındaki bilgi düzeylerinin belirlenmesi amacıyla yapılmıştır. Tanımlayıcı türdeki araştırmanın evrenini Gümüşhane Üniversitesi öğrencileri oluşturdu. Araştırmada 1500 öğrenciye ulaşılmıştır ve veri toplama formu olarak araştırmacılar tarafından hazırlanan anket formu kullanılmıştır. Araştırmaya katılan öğrencilerin yaş ortalaması 21.21±1.95'dir. Öğrencilerin %40,7'si sağlık bilimleri fakültesinde öğrenim görmektedir ve öğrencilerin %42.6'sını disleks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, their dyslexia knowledge and beliefs in the treatment and coping dimension were average. In a study conducted by Ulutasdemir et al (2021) to assess the level of knowledge about dyslexia among university students, it was revealed that 42.6% of the students reported having encountered or heard about dyslexia before, while the remaining participants had no prior knowledge of the concept. Similarly, in a study by Seckin-Yilmaz and Erim (2019) that examined the knowledge levels of adults about dyslexia, it was noted that the knowledge levels of adults regarding dyslexia were generally low, and their education levels did not significantly affect this situation.…”
Section: Discussionmentioning
confidence: 99%
“…However, their dyslexia knowledge and beliefs in the treatment and coping dimension were average. In a study conducted by Ulutasdemir et al (2021) to assess the level of knowledge about dyslexia among university students, it was revealed that 42.6% of the students reported having encountered or heard about dyslexia before, while the remaining participants had no prior knowledge of the concept. Similarly, in a study by Seckin-Yilmaz and Erim (2019) that examined the knowledge levels of adults about dyslexia, it was noted that the knowledge levels of adults regarding dyslexia were generally low, and their education levels did not significantly affect this situation.…”
Section: Discussionmentioning
confidence: 99%